Measurement of the anomalous like-sign dimuon charge asymmetry with 9fb-1 of pp̄ collisions - Abazov, V. M. (2011)
We present an updated measurement of the anomalous like-sign dimuon charge asymmetry Aslb for semileptonic b-hadron decays in 9.0fb-1 of pp̄ collisions recorded with the D0 detector at a center-of-mass energy of √s=1.96TeV at the Fermilab Tevatron collider. We obtain Aslb=(-0.787±0.172(stat)±0.093(syst))%. This result differs by 3.9 standard deviations from the prediction of the standard model and provides evidence for anomalously large CP violation in semileptonic neutral B decay. The dependence of the asymmetry on the muon impact parameter is consistent with the hypothesis that it originates from semileptonic b-hadron decays. © 2011 American Physical Society.